2005
DOI: 10.1016/j.curtheres.2005.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single-dose injectable paracetamolversus propacetamol in pain management after minor gynecologic surgery: A multicenter, randomized, double-blind, active-controlled, two-parallel-group study

Abstract: In these patients with moderate to severe pain after minor gynecologic surgery, a single dose of IV-APAP was associated with better local tolerability, similar analgesic efficacy, and greater patient satisfaction compared with a single bioequivalent dose of ProAPAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Previous trials have shown bioequivalence of paracetamol 1 g and propacetamol 2 g [6, 37]. Head‐to‐head trials of intravenous paracetamol vs. intravenous propacetamol have shown no differences in the proportion of participants achieving at least 50% pain relief during 4 postoperative hours [6, 36, 38, 39]. Only one included trial gave propacetamol compared with five doses of oral paracetamol [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous trials have shown bioequivalence of paracetamol 1 g and propacetamol 2 g [6, 37]. Head‐to‐head trials of intravenous paracetamol vs. intravenous propacetamol have shown no differences in the proportion of participants achieving at least 50% pain relief during 4 postoperative hours [6, 36, 38, 39]. Only one included trial gave propacetamol compared with five doses of oral paracetamol [31].…”
Section: Discussionmentioning
confidence: 99%
“…postoperative hours [6,36,38,39]. Only one included trial gave propacetamol compared with five doses of oral paracetamol [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More acetaminophen patients were also willing to receive the same treatment again (96% vs 81%, P = .005). 27…”
Section: Comparative Efficacymentioning
confidence: 99%
“…13 Pain relief is reached within 15 minutes of intravenous acetaminophen, 13,14 and it has been effective in controlling pain and reducing the need for narcotics in postoperative patients. [15][16][17][18][19][20][21] Clinical and anecdotal evidence demonstrates a greater analgesic effect for intravenous administration. 14 The goal of analgesia in labor is to reduce pain while minimizing both maternal and fetal adverse effects.…”
mentioning
confidence: 99%